Impact of ICTs on leadership practices: representations and actions. Issue 4 (1st June 2015) - Leduc, Sylvain; Guilbert, Laure; Vallery, Gérard
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to present the results of field research carried out within a civil army corps responsible for the security of people and property. Design/methodology/approach – The study deals with e-leadership as it leadership practices related to information and communication technologies (ICTs). Findings – Having initially described the position of ICTs in current workplace contexts, the authors review the question of the role of leadership as well as that of knowledge acquired in e-leadership. Practical implications – The results reveal variations in the use of ICTs in leadership situations, which find their origins in multiple determinisms related to the types of task, the technological tools and the constraints inherent to customary situations. Originality/value – These conclusions are discussed in the light of research centered on the predictive variables arising from the adoption of technologies in the context of the workplace.